Return to Work and Functional Outcomes After Major Trauma: Who Recovers, When, and How Well?. Issue 4 (April 2016) - Gabbe, Belinda J.; Simpson, Pamela M.; Harrison, James E.; Lyons, Ronan A.; Ameratunga, Shanthi; Ponsford, Jennie; Fitzgerald, Mark; Judson, Rodney; Collie, Alex; Cameron, Peter A.
Abstract : Objective: To describe the long-term outcomes of major trauma patients and factors associated with the rate of recovery. Background: As injury-related mortality decreases, there is increased focus on improving the quality of survival and reducing nonfatal injury burden. Methods: Adult major trauma survivors to discharge, injured between July 2007 and June 2012 in Victoria, Australia, were followed up at 6, 12, and 24 months after injury to measure function (Glasgow Outcome Scale—Extended) and return to work/study. Random-effects regression models were fitted to identify predictors of outcome and differences in the rate of change in each outcome between patient subgroups. Results: Among the 8844 survivors, 8128 (92%) were followed up. Also, 23% had achieved a good functional recovery, and 70% had returned to work/study at 24 months. The adjusted odds of reporting better function at 12 months was 27% (adjusted odds ratio 1.27, 95% confidence interval [CI] 1.19–1.36) higher compared with 6 months, and 9% (adjusted odds ratio 1.09, 95% CI, 1.02–1.17) higher at 24 months compared with 12 months. The adjusted relative risk (RR) of returning to work was 14% higher at 12 months compared with 6 months (adjusted RR 1.14, 95% CI, 1.12–1.16) and 8% (adjusted RR 1.08, 95% CI, 1.06–1.10) higher at 24 months compared with 12 months. Conclusions: Improvement in outcomes over the study period was observed, although ongoing disability was common at 24 months. Recovery trajectories differed by patient characteristics, providing valuable information for informing prognostication and service planning, and improving our understanding of the burden of nonfatal injury.